Co-existing pediatric ureteropelvic junction obstruction and vesicoureteric reflux: Prevalence and implications - Shalini Hegde; Prema Menon; Katragadda Lakshmi Narasimha Rao (Journal of Indian Association of Pediatric Surgeons, 2019)
Purpose: The purpose of this study is to ascertain the coexistence of ipsilateral vesicoureteric reflux (VUR) with ureteropelvic junction obstruction (UPJO) and to compare postpyeloplasty outcome in patients with and without associated VUR. Materials and Methods: Prospective study from 2014 to 2016 of consecutive children (n = 135) undergoing pyeloplasty. Data of patients without (Group 1) and with (Group 2) associated ipsilateral VUR were compared. Results: Thirty-five patients (25.9%) had ipsilateral VUR along with UPJO (Group 2). This group showed the following unique features: (1) Higher percentage of infants (31/35) compared to Group 1 (62/100) (P = 0.003) (2) VUR in the contralateral (normal) kidney in 21/35 (60%) cases and nil in Group 1 (3) Significantly less preoperative differential renal function in children above 1 year (P = 0.007) (4) Presence of renal scars (18 units) and pyelonephritic changes (6 units) in Group 2 at the 1-year follow-up dimercaptosuccinic acid renal scan. Both groups showed improvement in function 3 months after pyeloplasty with no statistically significant difference. Improvement in drainage on the renal scan was better in Group 1 at 3 months postoperative (P = 0.015) as well as between 3 months and 1-year follow-up (P = 0.052). Conclusion: The prevalence of VUR was 25.9% in this study and 33.3% in ≤1 year age group. There was a loss of function in delayed presenters with associated ipsilateral VUR. There was delayed drainage postpyeloplasty in patients with VUR. A preoperative voiding cystourethrogram should be done in children <1 year age before pyeloplasty so that associated VUR if detected can be concurrently managed along with pyeloplasty and preserve nephrons affected by the dual pathology.